ANALISIS STRATEGIS LOKASI USAHA TAHU SUMEDANG DI KOTA TIMIKA SP 2 - Novita Nasution; Tharsisius Pabendon (CV. ADIBA AISHA AMIRA, 2023)
The purpose of this study was to determine the strategic location of the Sumedang Tofu business based on the factors that influence the determination of the business location and to find out the things that need to be considered by the Sumedang Tofu business in order to maintain and increase its business value related to the business location. This research uses a qualitative descriptive method, and data collection methods use literature study, observation, and interviews. To analyze the problem of this research used the material index (IM) according to Alfred Weber and qualitative analysis. The results showed that the location of Sumedang SP 2 tofu business was not strategic